An Analysis of Use of Technology in Agriculture (International Journal of Food and Nutritional Sciences, 2022)
For decades, agriculture has been the most popular pastime. It is vital to the livelihood of many people. It employs a huge number of people, making it crucial to the Indian economy. It serves as the economic backbone of a nation. Many poor nations rely on it for their primary source of revenue. Preparing the land, planting seeds, adding manure and fertilizers, irrigation, harvesting the produce, and finally storing it are all examples of agricultural operations. Previously, humans were responsible for all of these tasks, but as the human population grows, so do people's need for various foods and crops. However, the increasing need for people could not be fulfilled using outdated techniques and technologies. As a result, numerous technical advancements in agriculture have occurred, including drones, robotics, vertical farming, organic farming, smart farming, sensors, trackers, and other innovations. These technologies have improved the efficiency of the agricultural industry by making crop output greater and quicker. In this article, the author discusses the many technologies that have been introduced and how they have affected the Indian economy's development.